Stress Levels among Anglican Clergy: The Beneficial Effects of Feeling Supported - Francis, Leslie J. (Journal of empirical theology, 2018)
The present study draws on data generated by the Church Growth Research Programme among 1,268 full-time stipendiary Church of England clergy aged 68 or under to test the extent to which the sense of feeling supported by professional advisers (positive affect) may offset the sense of feeling stressed (negative affect), after taking into account a range of personal, psychological, environmental and theological or ecclesial factors. The data found that the sense of feeling supported by professional advisers reduced the levels of self-reported stress after controlling for personal, psychological, environmental, and theological or ecclesial factors. The implications of these findings for the provision of formal support mechanisms within dioceses is discussed.